Improving Students’ Reading Comprehension by Using Story Pyramid and Plus Minus Interesting Strategy - Elfriman Gea; Erika Sinambela; Kammer Tuahman Sipayung (PALAPA, 2023)
This research shows that there were several problems faced by students at SMA Negeri 2 Alasa in learning English, especially learning reading comprehension. Therefore, researcher was interested in conducting research entitled " Improving Students’ Reading Comprehension by Using Story Pyramid and Plus Minus Interesting Strategy at the Tenth Grade of SMA Negeri 2 Alasa". This research aims to observe the learning difficulties of these students, whether using the Story Pyramid and Plus Minus Interesting strategies could improve reading comprehension skills of the tenth grade students at SMA Negeri 2 Alasa and find out which strategy was more effective in improving reading comprehension skills. In this research, the researcher used classroom action research (CAR). CAR is an examination of learning activities in the form of an action, which is carried out to improve the teaching and learning process so as to improve learning outcomes that are better than before. Based on the results of the analysis, the pre-test results in class X-IPS which used the Story Pyramid strategy obtained an average score of 61.05%, while in class X-IPA got 56,84%. After the students learned by using these two strategies, the average post-test score for class X-IPS was 73.68% and class X-IPA was 74.21%. From these calculations it was concluded that there was a significant improvement in students' scores in reading comprehension and the use of Plus Minus Interesting strategy was more effective in improving students' reading comprehension with an average score increase of 17.37% compared to Story Pyramid's 12.63%.